Intragastric infusion of denatonium benzoate attenuates interdigestive gastric motility and hunger scores in healthy female volunteers - Deloose, Eveline; Janssen, Pieter; Corsetti, Maura; Biesiekierski, Jessica; Masuy, Imke; Rotondo, Alessandra; Van Oudenhove, Lukas; Depoortere, Inge; Tack, Jan (American Society for Nutrition, 2017)
Background: Denatonium benzoate (DB) has been shown to influence ongoing ingestive behavior and gut peptide secretion. Objective: We studied how the intragastric administration of DB affects interdigestive motility, motilin and ghrelin plasma concentrations, hunger and satiety ratings, and food intake in healthy volunteers. Design: Lingual bitter taste sensitivity was tested with the use of 6 concentrations of DB in 65 subjects. A placebo or 1 μmol DB/kg was given intragastrically to assess its effect on fasting gastrointestinal motility and hunger ratings, motilin and ghrelin plasma concentrations, satiety, and caloric intake. Results: Women (n = 39) were more sensitive toward a lingual bitter stimulus (P = 0.005) than men (n = 26). In women (n = 10), intragastric DB switched the origin of phase III contractions from the stomach to the duodenum (P = 0.001) and decreased hunger ratings (P = 0.04). These effects were not observed in men (n = 10). In women (n = 12), motilin (P = 0.04) plasma concentrations decreased after intragastric DB administration, whereas total and octanoylated ghrelin were not affected. The intragastric administration of DB decreased hunger (P = 0.008) and increased satiety ratings (P = 0.01) after a meal (500 kcal) in 13 women without affecting gastric emptying in 6 women. Caloric intake tended to decrease after DB administration compared with the placebo (mean ± SEM: 720 ± 58 compared with 796 ± 45 kcal; P = 0.08) in 20 women. Conclusions: Intragastric DB administration decreases both antral motility and hunger ratings during the fasting state, possibly because of a decrease in motilin release. Moreover, DB decreases hunger and increases satiety ratings after a meal and shows potential for decreasing caloric intake